2010
DOI: 10.1177/030630701003500401
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Bankruptcy Filing Decisions

Abstract: This paper examines the nature and extent of potential linkages between corporate governance characteristics and bankruptcy filing decisions. To test the paper's research hypotheses and follow prior related literature, a sample of financially distressed firms was formed and matched with a group of financially healthy firms in the US between 2001 and 2003. Results show that in addition to lower business and financial health indicators faced by financially distressed firms compared to their financially healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 41 publications
6
54
1
Order By: Relevance
“…The presence of independent directors in the board of directors contributes in shortening the cash conversion cycle which favors American manufacturing firms because a shorter cash conversion cycle improves the efficiency of working capital management and consequently, the financial health the firm. Thus, this study lends some support to the findings of Daily and Dalton (1994); Fich and Slezak (2008); Lajili and Zéghal (2010);and Gill and Biger (2013) in that independent directors and corporate governance improve working capital management efficiency and the financial health of the firm.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The presence of independent directors in the board of directors contributes in shortening the cash conversion cycle which favors American manufacturing firms because a shorter cash conversion cycle improves the efficiency of working capital management and consequently, the financial health the firm. Thus, this study lends some support to the findings of Daily and Dalton (1994); Fich and Slezak (2008); Lajili and Zéghal (2010);and Gill and Biger (2013) in that independent directors and corporate governance improve working capital management efficiency and the financial health of the firm.…”
Section: Discussionsupporting
confidence: 71%
“…However, independent directors still are in a position to advise and support the board of directors, which assists in making sound working capital management and other important decisions that are useful in improving the financial health of the firm. Previous studies (Daily & Dalton, 1994;Fich & Slezak, 2008;Lajili & Zéghal, 2010) found that the percentage of independent directors positively affect the financial health of the firm. Foo and Zain (2010) took a sample of 481 companies listed on the Malaysian Stock Exchange and found that more independent and diligent boards are associated with higher liquidity.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…The evidence from studies on the relationship of corporate governance factors to corporate bankruptcy has been mixed (Daily & Dalton, 1994a, b;Darrat, Gray & Wu, 2010;Fich & Slezak, 2008;Lajili & Zéghal, 2010). Some studies find that bankrupt companies are more likely to have small boards of directors or lose directors as bankruptcy approaches (Darrat, et al, 2010;Gales & Kesner, 1994), while others find just the opposite (Fich & Slezak, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report that this duality is more prevalent in bankrupt firms (Daily & Dalton, 1994a, b;Darrat, et al, 2010), while others do not find this relationship to be predictive (Lajili & Zéghal, 2010). By contrast, the percentage of independent directors relates positively to corporate health (Daily & Dalton, 1994a, b;Darrat, et al, 2010;Fich & Slezak, 2008;Lajili & Zéghal, 2010). Gales and Kesner (1994) go further and observe that companies which fail have different board structures than companies which survive.…”
Section: Introductionmentioning
confidence: 99%